2010
DOI: 10.3349/ymj.2010.51.6.857
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Obesity and Bone Mineral Density and Vertebral Fractures in Korean Postmenopausal Women

Abstract: PurposeThe traditional belief that obesity is protective against osteoporosis has been questioned. Recent epidemiologic studies show that body fat itself may be a risk factor for osteoporosis and bone fractures. Accumulating evidence suggests that metabolic syndrome and the individual components of metabolic syndrome such as hypertension, increased triglycerides, and reduced high-density lipoprotein cholesterol are also risk factors for low bone mineral density. Using a cross sectional study design, we evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
2
26

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(128 citation statements)
references
References 39 publications
(38 reference statements)
7
90
2
26
Order By: Relevance
“…With the increasing incidence of obesity in the population [7,14] and recent evidence that there is a greater fracture incidence in obese patients [15,16] and lower than expected BMD in a sub-population of obese women [17], the larger precision errors in obese populations demonstrated in this study will be increasingly significant for clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing incidence of obesity in the population [7,14] and recent evidence that there is a greater fracture incidence in obese patients [15,16] and lower than expected BMD in a sub-population of obese women [17], the larger precision errors in obese populations demonstrated in this study will be increasingly significant for clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…High cholesterol fed rats had higher body weights, which is consistent with the view that obesity is related wtih osteoporosis. Kim [20] showed that high percentage body fat and waist circumference correlated with low BMD and risk of a vertebral fracture. Obesity-reduced bone density was associated with activation of PPARgamma and suppression of Wnt/ beta-catenin in rapidly growing male rats [21] .…”
Section: Discussionmentioning
confidence: 99%
“…that obesity is not benefi cial or has a negative eff ect on osteoporosis. In a study of postmenopausal Korean women 19 , waist circumference, which provides an indication of central obesity (visceral fat mass), was related to low BMD and osteoporotic vertebral fractures. In contrast, our research demonstrated signifi cant positive correlation between vertebral and femoral BMD and waist circumference, which could be explained by higher circulating insulin levels in central obesity.…”
Section: Discussionmentioning
confidence: 99%